If it's not what You are looking for type in the equation solver your own equation and let us solve it.
37-(14-x)=(x+2)-(6-x)
We move all terms to the left:
37-(14-x)-((x+2)-(6-x))=0
We add all the numbers together, and all the variables
-(-1x+14)-((x+2)-(-1x+6))+37=0
We get rid of parentheses
1x-((x+2)-(-1x+6))-14+37=0
We calculate terms in parentheses: -((x+2)-(-1x+6)), so:We add all the numbers together, and all the variables
(x+2)-(-1x+6)
We get rid of parentheses
x+1x+2-6
We add all the numbers together, and all the variables
2x-4
Back to the equation:
-(2x-4)
x-(2x-4)+23=0
We get rid of parentheses
x-2x+4+23=0
We add all the numbers together, and all the variables
-1x+27=0
We move all terms containing x to the left, all other terms to the right
-x=-27
x=-27/-1
x=+27
| 3x^2+2x^2=300 | | 5*x–10=102*x*2 | | x(x-30)+81=0 | | 1/8a=((a-5)/(8a^2))-((5a+15)/(8a^2)) | | -4(b+4)=8 | | -3(n-3)=18 | | -2(n+5)=24 | | 4,5x=16,29 | | -(-2+b)=2 | | -2(-3+v)=-6 | | r/8+5=6 | | -n+3=-5 | | 3(-4+x)=-3 | | 1+r/2=6 | | -4-v=-12 | | -4(m-2)=4 | | -1-4x=17 | | 2+p/10=1 | | -4a-2=34 | | -2(4+x)=10 | | m/4-1=1 | | -2-5p=-47 | | 2*x^2+x-100=0 | | 12x-24=(-12+21x)-(12x-24) | | (1m/2+2m/3)(1/2-2m/3)=0 | | 21x-10=29x-82 | | 4/5x=3/2 | | 2(q-12)-5=1 | | 6x-24=60+4x | | 7x-3x+2x=24 | | 2x+4x-5x=45 | | 1.6y+1.78=-1.26 |